COMPARISON OF TACTICAL AND TECHNICAL TEACHING APPROACHES AND THEIR INFLUENCE ON THE LEVEL OF VOLLEYBALL PERFORMANCE OF PUPILS AGED 13 AND 14 - Jaroslav Popelka (Sport Scientific And Practical Aspects, 2025)
The study presents the results of experimental research which was aimed at investigating and verifying the impact of a specific programme on the levels of change in volleyball performance of pupils aged 13 and 14. This pedagogical experiment was used in the research as a dominant method. The evaluation was carried out by means of logical, mathematical and statistical methods. The obtained data pointed out the fact that tactical and technical approaches of teaching lead to similar levels of performance. However, our research showed that tactical approach has a more positive impact on learning tactics and the ability of pupils to apply them during the game.